Neuroimaging and DNA Methylation: An Innovative Approach to Study the Effects of Early Life Stress on Developmental Plasticity - Mariani Wigley, Isabella Lucia Chiara; Mascheroni, Eleonora; Peruzzo, Denis; Giorda, Roberto; Bonichini, Sabrina; Montirosso, Rosario (Frontiers in Psychology, 2021)
DNA methylation plays a key role in neural cell fate and provides a molecular link between early-life stress and later-life behavioral phenotypes. Here, studies that combine neuroimaging methods and DNA methylation analysis in pediatric population with a history of adverse experiences were systematically reviewed focusing on: targeted genes and neural correlates; statistical models used to examine the link between DNA methylation and neuroimaging data also considering early-life stress and behavioral outcomes. We identified 8 studies that report associations between DNA methylation and brain structure/functions in infants, school age children and adolescents faced with early-life stress condition (e.g., preterm birth, childhood maltreatment, low socioeconomic status and less-than optimal caregiving). Results showed that several genes were investigated (e.g., OXTR, SLC6A4, FKBP5, BDNF) and different neuroimaging techniques were performed (MRI and f-NIRS). Statistical model used ranged from correlational to more complex moderated mediation models. Most of the studies (n = 5) considered DNA methylation and neural correlates as mediators in the relationship between early-life stress and behavioral phenotypes. Understanding what role DNA methylation and neural correlates play in interaction with early-life stress and behavioral outcomes is crucial to promote theory-driven studies as the future direction of this research fields.